EFEKTIVITAS KOMUNIKASI INTERPERSONAL ANTARA PERAWAT DAN PASIEN RAWAT INAP DI RUMAH SAKIT TIPE B ANDI MAKKASAU KOTA PAREPARE - Rani Ulansari; Iskandar Iskandar (KOMUNIDA : Media Komunikasi dan Dakwah, 2016)
This research focus to examine how patterns of interpersonal communication between nurses and patients in hospitals Type B Andi Makkasau and how the effectiveness of interpersonal communication between nurses and patients. The purpose of this study to determine the pattern and effectiveness of interpersonal communication between nurses and patients in hospitals Type B Andi Makkasau. This study was conducted at Hospital Type B Andi Makkasau, Jln. Nurussamawati No. 9 Parepare South Sulawesi. The research method used descriptive qualitative method in the form of words, written or spoken of and behaviors that can be observed as the unit of analysis Interpersonal Communication Between Nurses and Inpatient. The results showed that the patterns of communication that is built in Makkasau Andi Type B hospitals, nurses use a dangling carrot pattern that is more promising rewards nurses to pediatric patients. Jams were also constructed pattern is the pattern of many catalysts provide motivation, support to recover. While the effectiveness of communication in viewing convenience of the patient and the spirit to heal and rapid healing process is felt by the patient. Nurses still consider when treating patients remember the five S (greetings, greetings, smiles, polite, Satun).